Efficacy of Two Radiologic‐Assisted Prophylactic Gastropexy Techniques. Issue 4 (23rd March 2016) - Balsa, Ingrid M.; Culp, William T. N.; Johnson, Eric G.; Glaiberman, Craig B.; Grimes, Millie; Mayhew, Philipp D.; Palm, Carrie A.
Abstract : Objective: To describe the technique and clinical outcome of prophylactic percutaneous radiologic‐assisted gastropexy (PRG) and radiologic‐assisted incisional gastropexy (RIG) in client‐owned dogs. Study Design: Prospective, nonrandomized clinical trial. Animals: Fourteen client‐owned, large, and giant breed dogs. Methods: Four dogs underwent PRG with fluoroscopic guidance to place 2 T‐fasteners into the pyloric antrum and secure it to the right body wall. Ten dogs underwent RIG, which was a modification of PRG. For RIG, the T‐fasteners were first used to approximate the pyloric antrum and body wall, then a full thickness incision through the body wall was made and the pyloric antrum was sutured to the internal abdominal wall. The duration and complications of each procedure were recorded. The gastropexy was assessed by abdominal ultrasound at day 1, week 2, and week 8 postoperative and by barium gastrogram at week 8 postoperative. Results: No dogs undergoing PRG had a gastropexy present at week 2. All dogs undergoing RIG had ultrasonographic evidence of gastropexy at day 1, week 2, and week 8 postoperative. Gastrograms in 9/9 dogs were consistent with an intact gastropexy, appropriate gastric positioning and appropriate gastric emptying began. No major complications were noted. Conclusion: The PRG was unsatisfactory and did not result in a permanent gastropexy. The RIG was safe and created a gastropexy that remained intact at 8 weeks postoperative. The RIG should be considered as a minimally invasive option for prophylactic gastropexy in dogs of at‐risk breeds.